2021
DOI: 10.1111/crj.13383
|View full text |Cite|
|
Sign up to set email alerts
|

Dexmedetomidine combined with midazolam infusion guided by bispectral index during bronchoscopy

Abstract: Background Conscious sedation guided by bispectral index (BIS) during bronchoscopy has been proved to be a feasible approach. This study aimed to investigate the safety and efficacy of dexmedetomidine combined with midazolam for undergoing conscious sedation during bronchoscopy. Methods The trial was registered prior to patient enrollment at the Chinese Clinical Trial Registry. Patients were randomized into DEX group (dexmedetomidine combined with midazolam) and FEN group (fentanyl combined with midazolam). Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
(49 reference statements)
0
7
0
Order By: Relevance
“…Finally, the level of physician satisfaction was signi cantly lower in the DEX group. The results of this study join a large number of small RCTs that were conducted in recent years, with diverse results regarding respiratory and hemodynamic outcomes [16][17][18][19][20][21][22][23][24][25][26][27]. For a more accurate and concise view of recent published results and to mitigate the current study's limitations (i.e., small sample size and lack of blinding), we conducted a systematic review and meta-analysis of all RCTs that evaluated the e cacy of DEX during bronchoscopy and included the results of the current trial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the level of physician satisfaction was signi cantly lower in the DEX group. The results of this study join a large number of small RCTs that were conducted in recent years, with diverse results regarding respiratory and hemodynamic outcomes [16][17][18][19][20][21][22][23][24][25][26][27]. For a more accurate and concise view of recent published results and to mitigate the current study's limitations (i.e., small sample size and lack of blinding), we conducted a systematic review and meta-analysis of all RCTs that evaluated the e cacy of DEX during bronchoscopy and included the results of the current trial.…”
Section: Discussionmentioning
confidence: 99%
“…During the period from 2012 to 2021 eleven more RCTs were conducted to evaluate DEX during bronchoscopy in comparison to propofol, midazolam and fentanyl in various combinations. While some of these trials reported a lower rate of desaturation events and an adequate sedation level, others reported no difference in desaturation events, a higher rate of hemodynamic adverse events and an inferior level of patient sedation and bronchoscopist satisfaction [17][18][19][20][21][22][23][24][25][26][27]. Therefore, DEX sedation for bronchoscopy is considered an emerging method for sedation during bronchoscopy.…”
Section: Sedation Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of the literature shows 12 published RCT’s that evaluated DEX sedation for bronchoscopy [ 16 27 ]. Four trials evaluated DEX for conscious sedation and administered the drug only once at the beginning of the procedure [ 17 , 23 , 25 , 26 ]. The largest of these trials by Zhang et al reported a lower rate of desaturation events in the DEX group however, with a higher rate of adverse events, correspondingly to the current trial.…”
Section: Discussionmentioning
confidence: 99%
“…During the period from 2012 to 2021 eleven more RCTs were conducted to evaluate DEX during bronchoscopy, in comparison to propofol, midazolam and fentanyl, in various combinations. While some of these trials reported a lower rate of desaturation events and an adequate sedation level, others reported no difference in desaturation events, a higher rate of hemodynamic adverse events and an inferior level of patient sedation and bronchoscopist satisfaction [ 17 27 ]. Therefore, DEX sedation for bronchoscopy is considered an emerging method for sedation during bronchoscopy.…”
Section: Introductionmentioning
confidence: 99%